The Prognostic Role of In-Hospital Mortality Predictors and De Ritis Ratio in Patients with Upper Gastrointestinal System Bleeding - Ayşenur Uçar, Aynur Doğrusöz (Pakistan Journal of Medical & Health Sciences, 2022)
Material-Method: In our tertiary hospital’s intensive care unit, we studied the clinical and laboratory records of 243 patients who had been admitted with upper GIS bleeding between January 2018 and April 2022. Results: Patients with upper gastrointestinal haemorrhage who were hospitalised were 65.8% male (M/F: 56/22). Mean age was 68.611.56 years old. One cutoff value was determined for the De Ritis ratio: 1.54. The mortality rate within the hospital was 13.1%.. Conclusion: Our results showed for the first time that the De Ritis ratio was not associated with in-hospital mortality in GI bleeding but further large clinical studies are needed to examine this issue.